Dissecting tripartite synapses with STED microscopy - Panatier, Aude (The Royal Society, 2014)
The concept of the tripartite synapse reflects the important role that astrocytic processes are thought to play in the function and regulation of neuronal synapses in the mammalian nervous system. However, many basic aspects regarding the dynamic interplay between pre- and postsynaptic neuronal structures and their astrocytic partners remain to be explored. A major experimental hurdle has been the small physical size of the relevant glial and synaptic structures, leaving them largely out of reach for conventional light microscopic approaches such as confocal and two-photon microscopy. Hence, most of what we know about the organization of the tripartite synapse is based on electron microscopy, which does not lend itself to investigating dynamic events and which cannot be carried out in parallel with functional assays. The development and application of superresolution microscopy for neuron–glia research is opening up exciting experimental opportunities in this regard. In this paper, we provide a basic explanation of the theory and operation of stimulated emission depletion (STED) microscopy, outlining the potential of this recent superresolution imaging modality for advancing our understanding of the morpho-functional interactions between astrocytes and neurons that regulate synaptic physiology.